Comprehensive proteomic profiling of intestinal tissues in patients with ulcerative colitis - Wang, Huiling; Xie, Qi; Xie, Yi; Luo, Weiguang (Frontiers in Medicine, 2025)
IntroductionUlcerative colitis (UC) is a chronic inflammatory bowel disease characterized by persistent inflammation of the colonic mucosa. This condition can significantly affect the quality of life of those affected. While UC is common, its underlying mechanisms are not yet fully understood, highlighting the need for a comprehensive proteomic analysis of intestinal tissues to identify potential biological changes associated with the disease. This study aimed to investigate the proteomic differences in the intestinal tissues of patients with UC and healthy individuals using high-throughput liquid chromatography–tandem mass spectrometry (LC–MS/MS) and bioinformatics methods.MethodsThe study employed a comprehensive proteomic analysis using LC–MS/MS to identify protein expression differences in intestinal tissues from five patients with UC versus five healthy controls. Subsequent bioinformatics analyses, including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses, elucidated altered biological processes.ResultsWe identified 194 upregulated and 323 downregulated proteins in the tissues of patients with UC, indicating a significant difference in protein expression. GO analysis revealed that the upregulated proteins were mainly involved in immune responses and metabolic processes, while the downregulated proteins were associated with organic and cellular metabolism. Additionally, KEGG pathway analysis showed that upregulated proteins were enriched in pathways related to ribosomes and phagosomes, whereas downregulated proteins were primarily linked to oxidative phosphorylation, thermogenesis, and the citric acid cycle, pointing to substantial changes in cellular energy metabolism. Protein–protein interaction (PPI) network analysis identified several key nodes, particularly those connected to ribosomal and phagocytic functions, which may play significant roles in the pathophysiology of UC.ConclusionThis study offers new insights into the biological mechanisms underlying UC and lays the foundation for future therapeutic strategies targeting these proteomic changes. Further experimental validation and clinical investigations are necessary to uncover additional mechanisms of UC and to facilitate the development of effective treatments.